Educação matemática nos cursos de licenciatura em educação do campo no Rio Grande do Sul: diálogos com professores formadores - Santos, Maluza Gonçalves dos (2017)
The present research investigates the structure of presential courses in Field Education Degree in Rio Grande do Sul and the involvement of teachers from the most varied areas of knowledge, among them, the training teachers of the curricular component focused on Mathematics. The main objective of this study is to analyze the formative process of the Degree courses in Field Education - Natural Sciences in the light of Bakhtin's studies, in the dialogical perspective, in three Higher Education Institutions of Rio Grande do Sul. In this perspective, dialogues are woven with the trainer teachers of the curricular component oriented to Mathematics to understand how the interaction of the different areas of knowledge occurs. For that, supported by the theoretical methodological contribution to Bakhtin’s dialogical theory, we approach the concepts of dialogism, alterity and act; A new and challenging world when the field of linguistics is adopted. The Field Education Degree is considered as an emerging degree, given by the relevance of the social movements concretized by a multiplicity of voices that echoed through Brazil, becoming a reality. What exists at the present moment is a projection of egress, with the differential of recovering and valuing the different knowledges and promoting the approximation of social and cultural practices of life in the field with the scientific knowledge. The research appealed to the theoretical basis of the historical retake of the Field Education topic in Brazil, the course of the Field Education Movement, the implementation policies of this course, the organization of the curriculum respecting the time of the field through the Alternation Pedagogy, the integration of several knowledge and the possibilities of articulation with Mathematics Education. It is a research with a qualitative approach, characterized as exploratory and descriptive, which had as instruments of information gathering the semi-structured interview with the trainer teachers, the dialogue with the students of one of the institutions and topics of the follow-up of the School-Time, carried out in one of the participating institutions of the research, looking to learn the complex training process developed in this new modality of graduation. The analyzed data points out that there is a dialogic relation between the discourse of the trainer teachers who form the curricular component of Mathematics, protagonists of this story, fully responsive to their actions, and other assertions whose interlocutors are the other teachers, that are consolidating a degree course with many peculiarities, in a formative process that has the differential advocated by interdisciplinarity.